PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI HOTEL CROWNE PLAZA JAKARTA - Anis Tyantini Eka Putri; Salman Paludi (Human Capital Development, 2017)
Purpose- This study aimed to determine the effect of the variabel leadership and motivation on employee Perfomance at Crowne Plaza Hotel Jakarta. Design/methodology/approach- The population used in this study are employee of Crowne Plaza Jakarta. The method of analysis used in this study is the Multiple Linear Regression Test with SPSS (Statistical Product and Service Solution) version 20. Sample using accidential methode. Data were collected through questionnaires, then analyzed statistically. Findings- The result showed that the variation in the independent variable (leadership and motivation) used in this study is able to explain 84.64% of variation in the dependent variable (employee perfomance). While the remaining 16,36% which is influenced by other variables not included in this study.